The Relationship Between Teachers' Organizational Commitment and Career Anxiety - Alagoz, Tugba; Inandi, Yusuf; Gunduz, Yueksel (Izzet Kara, 2025)
In this study, it was aimed to examine the relationship between teachers' organizational commitment and career anxiety. A cross-sectional correlational design belonging to the relational survey model was used. A simple random sampling method was utilized to determine the sample. The sample consisted of 384 teachers. Personal Information Form, Teachers' Career Anxiety Scale, and Organizational Commitment Scale were applied to collect the data. In data analysis, descriptive statistics, Pearson correlation and regression analysis were used. In the study, teachers' perceptions of career anxiety were found to be high, and their perceptions of organizational commitment were found to be moderate. A negative and lower significant relationship was found between teachers' career anxiety and organizational commitment. It was determined that teachers' career anxiety scores could be significantly predicted by their organizational commitment responses. It was concluded that in order to increase the organizational commitment of teachers, it is necessary to realize their career anxiety reasons and levels. Suggestions were made to prevent the factors that hinder organizational commitment and to decrease the career anxiety of teachers.
Alagöz, Tuğba/0000-0003-4300-2076; İnandi, Yusuf/0000-0003-2760-0957
Keywords: Career Anxiety; Teachers; Organizational Commitment